Η σχετιζόμενη με την υγεία ποιότητα ζωής ατόμων με νεανική ιδιοπαθή αρθρίτιδα - Θωμά, Μαρία (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction : Juvenile idiopathic arthritis ( JIA ) is a frequently displayed chronic childhood disease . The NIA occurs in various forms burdening the health-related quality of life of patients . Purpose : To investigate the HRQOL of people with JIA , the relationship of various factors and the effectiveness of specific therapeutic agents. Material and Methods: A systematic literature search was done with the search tool "Pantognostis", which has access to electronic databases such as «PubMed, CINAHL, GOOGLE SCHOLAR» with the keywords " Juvenile Idiopathic Arthritis , quality of life , health-related quality of life , factors associated with quality of life , efficacy of drugs " in all possible combinations (AND, OR), from 2008 to 2014 . In the present study , there were included 13 research articles and 4 literature reviews. Results : It seems that the NIA has negatively affects in all aspects of HRQOL people who have this disease . Nevertheless, the use of therapeutic formulation as etanercept and methotrexate positively affect HRQOL in people with JIA . However, it is necessary to give more emphasis on improving the HRQOL of people with JIA and to find more programs and therapeutic intervention with the aim of ensuring a better quality of life related to health.
Keywords: Juvenile Idiopathic Arthritis; Quality of Life; Juvenile Idiopathic Arthritis; Ποιότητα Ζωής